2010
DOI: 10.1111/j.1365-2958.2010.07093.x
|View full text |Cite
|
Sign up to set email alerts
|

Septum formation is regulated by the RHO4‐specific exchange factors BUD3 and RGF3 and by the landmark protein BUD4 in Neurospora crassa

Abstract: SummaryRho GTPases have multiple, yet poorly defined functions during cytokinesis. By screening a Neurospora crassa knock-out collection for Rho guanine nucleotide exchange factor (GEF) mutants that phenocopy rho-4 defects (i.e. lack of septa, slow growth, abnormal branching and cytoplasmic leakage), we identified two strains defective in homologues of Bud3p and Rgf3 of budding and fission yeast respectively. The function of these proteins as RHO4-specific GEFs was determined by in vitro assays. In vivo micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 74 publications
5
93
1
1
Order By: Relevance
“…Finally, our genetic and biochemical analyses clearly establish that AnBud3 serves as a GEF that promotes activation of Rho4. A similar relationship between Bud3 and Rho4 has recently been described for another filamentous ascomycete fungus, N. crassa ( Justa-Schuch et al 2010). In this case, Bud3 also acts as a GEF for Rho4, which in turn directs assembly of the CAR at septation sites (Rasmussen and Glass 2005).…”
Section: Discussionmentioning
confidence: 84%
“…Finally, our genetic and biochemical analyses clearly establish that AnBud3 serves as a GEF that promotes activation of Rho4. A similar relationship between Bud3 and Rho4 has recently been described for another filamentous ascomycete fungus, N. crassa ( Justa-Schuch et al 2010). In this case, Bud3 also acts as a GEF for Rho4, which in turn directs assembly of the CAR at septation sites (Rasmussen and Glass 2005).…”
Section: Discussionmentioning
confidence: 84%
“…AFUA_5G07430 is similar to the GEFs SpRgf3 (S. pombe Rgf3) and NcRGF3 (N. crassa RGF3) of S. pombe and N. crassa, respectively. SpRgf3 is a GEF of SpRho1 and controls ␤-(1,3)-D-glucan biosynthesis and cytokinesis (17,18,28), while NcRGF3 of the filamentous fungus N. crassa was shown to be a specific GEF of NcRHO4 and controls septum formation (29). In this study, we focused on analyzing Rom2.…”
Section: Resultsmentioning
confidence: 99%
“…In A. nidulans, A. nidulans Bud3 (AnBud3) is a GEF of AnRho4 and essential for septum formation (36), and in N. crassa, even two nonredundant GEFs of NcRHO4 were identified, NcBUD3 and NcRGF3 (29). NcRGF3 is the homologue of AFUA_5G07430 which has a domain structure similar to Rom2 but is currently uncharacterized in Aspergillus.…”
Section: Discussionmentioning
confidence: 99%
“…Rasmussen and Glass further showed that RHO-4 localizes to septa and identified a difference in the regulation of septation during conidiation versus vegetative septation in N. crassa (44,45). Recent studies in N. crassa and A. nidulans indicate that RHO-4 localizes to septa and to the plasma membrane and is involved in signaling pathways that regulate septum formation (19,58).…”
Section: Discussionmentioning
confidence: 99%